A common bean truncated CRINKLY4 kinase controls gene-for-gene resistance to the fungus Colletotrichum lindemuthianum. (6th March 2021) - Richard, Manon M S; Gratias, Ariane; Alvarez Diaz, Juan C; Thareau, Vincent; Pflieger, Stéphanie; Meziadi, Chouaib; Blanchet, Sophie; Marande, William; Bitocchi, Elena; Papa, Roberto; Miklas, Phillip N; Geffroy, Valérie
Abstract : CRINKLY4 receptor-like kinases normally function in plant vascular development. We report a CRINKLY4 kinase in a truncated form with an unexpected role in resistance to Colletotrichum lindemuthianum in common bean. Abstract: Identifying the molecular basis of resistance to pathogens is critical to promote a chemical-free cropping system. In plants, nucleotide-binding leucine-rich repeat constitute the largest family of disease resistance ( R ) genes, but this resistance can be rapidly overcome by the pathogen, prompting research into alternative sources of resistance. Anthracnose, caused by the fungus Colletotrichum lindemuthianum, is one of the most important diseases of common bean. This study aimed to identify the molecular basis of Co-x, an anthracnose R gene conferring total resistance to the extremely virulent C. lindemuthianum strain 100. To that end, we sequenced the Co-x 58 kb target region in the resistant JaloEEP558 ( Co-x ) common bean and identified KTR2/3, an additional gene encoding a truncated and chimeric CRINKLY4 kinase, located within a CRINKLY4 kinase cluster. The presence of KTR2/3 is strictly correlated with resistance to strain 100 in a diversity panel of common beans. Furthermore, KTR2/3 expression is up-regulated 24 hours post-inoculation and its transient expression in a susceptible genotype increases resistance to strain 100. Our results provide evidence that Co-x encodes a truncated and chimeric CRINKLY4 kinase probably resulting from an unequal recombination event that occurred recently in the Andean domesticated gene pool. This atypical R gene may act as a decoy involved in indirect recognition of a fungal effector.